Analytical and Experimental Study on Composite Deep beams with Rolled section reinforcement - Pavani, Konuri; Harsha, G. Sri (International Journal of Engineering and Technology, 2018)
An experimental study was conducted on three RC Deep beams along with Analytical simulation under three point loading in which one specimen was provided with Rolled section reinforcement. The specimens are designed according to IS 456:2000 . In one specimen the total reinforcement area was replaced with rolled I-Section. Steel plate grade of MS250 of 3mm thickness was molded as rolled I- Section. Various parameters like flexural behavior, shear strength, deflection, crack width, stress and ductility were calculated. For improving the bond strength between steel section and concrete in composite member, shear struts are provided. The length to depth ratio (l/d) was 1.875 and shear span to depth ratio (a/d) was 0.75. Finite element simulation was carried out by using ANSYS 18.1. and comparison was madeÂ in between Analytical and Experimental results.Â